Social media and disaster management by the National Emergency Management in Nigeria: What it is and what it should be - Kasim, Oluwasinaayomi Faith; Oyerinde, Ismail Adedapo (Journal of Emergency Management, 2024)
The environment for communicating about emergencies and disasters has changed as a result of the development of mobile technologies and social media applications. The public expects emergency management agencies to monitor, respond to, and report disasters via mobile applications due to this shift. This study, using the retrospective approach, analyzes the posts by the National Emergency Management Agency (NEMA) on social media in Nigeria. Activities reported via the agency’s verified social media handles (Facebook®) between 2015 and 2021 serve as the data source. Findings revealed that social media is a useful tool in disaster management, as disaster-related activities and events across the management cycle were posted by NEMA’s national and zonal offices. Most posts (45.0 percent) focused on response activities, while the recovery phase (2.0 percent) had the least posts. There was a significant variation in the reporting across the disaster management cycle (F(4,30) = 9.746). Attention should be placed on shifting NEMA from post-disaster activities to a predisaster-focused agency. Therefore, the agency should develop a social media policy and train its information officers to use the medium to engage actively with the public, especially regarding information on predisaster management activities.